2021
DOI: 10.4269/ajtmh.20-1536
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Abnormalities in COVID-19: A Narrative Review

Abstract: COVID-19 is caused by SARS-CoV-2. Although pulmonary manifestations have been identified as the major symptoms, several hematological abnormalities have also been identified. This review summarizes the reported hematological abnormalities (changes in platelet, white blood cell, and hemoglobin, and coagulation/fibrinolytic alterations), explores their patho-mechanisms, and discusses its management. Common hematological abnormalities in COVID-19 are lymphopenia, thrombocytopenia, and elevated D-dimer levels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 136 publications
5
107
0
14
Order By: Relevance
“…A temporal trend of lowering PLT counts in COVID-19 patients could indicate a worsening thrombotic state [ 87 , 88 , 89 , 90 ]. It was reported that a PTL count <200 × 10 9 /L at admission was related to a threefold higher mortality rate [ 91 ]. On the other hand, improvement of thrombocytopenia in COVID-19 patients can indicate clinical progress [ 91 ].…”
Section: Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…A temporal trend of lowering PLT counts in COVID-19 patients could indicate a worsening thrombotic state [ 87 , 88 , 89 , 90 ]. It was reported that a PTL count <200 × 10 9 /L at admission was related to a threefold higher mortality rate [ 91 ]. On the other hand, improvement of thrombocytopenia in COVID-19 patients can indicate clinical progress [ 91 ].…”
Section: Plateletsmentioning
confidence: 99%
“…It was reported that a PTL count <200 × 10 9 /L at admission was related to a threefold higher mortality rate [ 91 ]. On the other hand, improvement of thrombocytopenia in COVID-19 patients can indicate clinical progress [ 91 ]. It was also reported that patients with severe COVID-19 displayed a higher degree of PTs activation, PLT–monocyte aggregation, and PLT–lymphocyte ratio (PLR) [ 88 , 92 , 93 , 94 ].…”
Section: Plateletsmentioning
confidence: 99%
“…The most common hematological findings in patients with COVID-19 include reduced lymphocyte count, while the platelet count differs according to the severity of the disease as well as the total number of the white blood cell count [ 7 , 8 , 9 ]. Severe lymphopenia was linked to more severe disease compared to milder lymphopenia, although leukocytosis was referred as an indication of severe inflammation process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being commonly associated with hypercoagulability, COVID-19 is also associated with thrombocytopenia [12]. Therefore, a full blood count is mandated before providing neuraxial anaesthesia.…”
Section: Introductionmentioning
confidence: 99%